Noble metals in oncology - Markowska, Anna; Kasprzak, Bartosz; Jaszczyńska-Nowinka, Karolina; Lubin, Jolanta; Markowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2015)
Worldwide research groups are searching for anticancer compounds, many of them are organometalic complexes having platinum group metals as their active centers. Most commonly used cytostatics from this group are cisplatin, carboplatin and oxaliplatin. Cisplatin was used fot the first time in 1978, from this time many platinum derivatives were created. In this review we present biological properties and probable future clinical use of platinum, gold, silver, iridium and ruthenium derivatives. Gold derivative Auranofin has been studied extensively. Action of silver nanoparticles on different cell lines was analysed. Iridium isotopes are commonly used in brachyterapy. Ruthenium compound new anti-tumour metastasis inhibitor (NAMI-A) is used in managing lung cancer metastases. Electroporation of another ruthenium based compound KP1339 was also studied. Most of described complexes have antiproliferative and proapoptotic properties. Further studies need to be made. Nevertheless noble metal based chemotherapheutics and compounds seem to be an interesting direction of research.